Laser-based technique for controlled damage of mesenchymal cell spheroids: a first step in studying reparation in vitro - Kosheleva, N. V. (Biol Open, 2016)
Modern techniques of laser microsurgery of cell spheroids were used to develop a new simple reproducible model for studying repair and regeneration in vitro. Nanosecond laser pulses (wavelength 355 nm, frequency 100 Hz, pulse duration 2 ns) were applied to perform a microdissection of the outer and the inner zones of human bone marrow multipotent mesenchymal stromal cells (BM MMSC) spheroids. To achieve effective dissection and preservation of spheroid viability, the energy of laser pulses was optimized and adjusted in the range 7-9 μJ. After microdissection, the edges of the wound surface opened and the angular opening reached a value of more than 180°. The destruction of the initial spheroid structure was observed in the wound area, with surviving cells changing their shape into a round one. Partial restoration of a spheroid form took place in the first six hours. The complete structure restoration accompanying the reparative processes occurred gradually over seven days due to remodelling of surviving cells.